Synthesis and reactivity of calix[4]arene-supported group 4 imido complexes. - Dubberley, SR; Friedrich, A; Willman, D; Mountford, P; Radius, U (2003)
New mononuclear titanium and zirconium imido complexes [M(NR)(R'(2)calix)] [M=Ti, R'=Me, R=tBu (1), R=2,6-C(6)H(3)Me(2) (2), R=2,6-C(6)H(3)iPr(2) (3), R=2,4,6-C(6)H(2)Me(3) (4); M=Ti, R'=Bz, R=tBu (5), R=2,6-C(6)H(3)Me(2) (6), R=2,6-C(6)H(3)iPr(2) (7); M=Zr, R'=Me, R=2,6-C(6)H(3)iPr(2) (8)] supported by 1,3-diorganyl ether p-tert-butylcalix[4]arenes (R'(2)calix) were prepared in good yield from the readily available complexes [MCl(2)(Me(2)calix)], [Ti(NR)Cl(2)(py)(3)], and [Ti(NR)Cl(2)(NHMe(2))(2)]. The crystallographically characterised complex [Ti(NtBu)(Me(2)calix)] (1) reacts readily with CO(2), CS(2), and p-tolyl-isocyanate to give the isolated complexes [Ti[N(tBu)C(O)O](Me(2)calix)] (10), [[Ti(mu-O)(Me(2)calix)](2)] (11), [[Ti(mu-S)(Me(2)calix)](2)] (12), and [Ti[N(tBu)C(O)N(-4-C(6)H(4)Me)](Me(2)calix)] (13). In the case of CO(2) and CS(2), the addition of the heterocumulene to the Ti-N multiple bond is followed by a cycloreversion reaction to give the dinuclear complexes 11 and 12. The X-ray structure of 13.4(C(7)H(8)) clearly establishes the N,N'-coordination mode of the ureate ligand in this compound. Complex 1 undergoes tert-butyl/arylamine exchange reactions to form 2, 3, [Ti(N-4-C(6)H(4)Me)(Me(2)calix)] (14), [Ti(N-4-C(6)H(4)Fc)(Me(2)calix)] (15) [Fc=Fe(eta(5)-C(5)H(5))(eta(5)-C(5)H(4))], and [[Ti(Me(2)calix)](2)[mu-(N-4-C(6)H(4))(2)CH(2)]] (16). Reaction of 1 with H(2)O, H(2)S and HCl afforded the compounds [[Ti(mu-O)(Me(2)calix)](2)] (11), [[Ti(mu-S)(Me(2)calix)](2)] (12), and [TiCl(2)(Me(2)calix)] in excellent yields. Furthermore, treatment of 1 with two equivalents of phenols results in the formation of [Ti(O-4-C(6)H(4)R)(2)(Me(2)calix)] (R=Me 17 or tBu 18), [Ti(O-2,6-C(6)H(3)Me(2))(2)(Me(2)calix)] (19) and [Ti(mbmp)(Me(2)calix)] (20; H(2)mbmp=2,2'-methylene-bis(4-methyl-6-tert-butylphenol) or CH(2)([CH(3)][C(4)H(9)]C(6)H(2)-OH)(2)). The bis(phenolate) compounds 17 and 18 with para-substituted phenolate ligands undergo elimination and/or rearrangement reactions in the nonpolar solvents pentane or hexane. The metal-containing products of the elimination reactions are dinuclear complexes [[Ti(O-4-C(6)H(4)R)(Mecalix)](2)] [R=Me (23) or tBu (24)] where Mecalix=monomethyl ether of p-tert-butylcalix[4]arene. The products of the rearrangement reaction are [Ti(O-4-C(6)H(4)Me)(2) (paco-Me(2)calix)] (25) and [Ti(O-4-C(6)H(4)tBu)(2)(paco-Me(2)calix)] (26), in which the metallated calix[4]arene ligand is coordinated in a form reminiscent of the partial cone (paco) conformation of calix[4]arene. In these compounds, one of the methoxy groups is located inside the cavity of the calix[4]arene ligand. The complexes 24, 25 and 26 have been crystallographically characterised. Complexes with sterically more demanding phenolate ligands, namely 19 and 20 and the analogous zirconium complexes [Zr(O-4-C(6)H(4)Me)(2)(Me(2)calix)] (21) and [Zr(O-2,6-C(6)H(3)Me(2))(2)(Me(2)calix)] (22) do not rearrange. Density functional calculations for the model complexes [M(OC(6)H(5))(2)(Me(2)calix)] with the calixarene possessing either cone or partial cone conformations are briefly presented.